The influence of internal and external factors on farmers' perception and participation in Jeneberang watershed conservation - Nuraeni,; Muchdar, Aminah; Basri, Lambang; Jusoff, Kamaruzaman; D., Muhammad Basri (IDOSI Publications, 2013)
The land conditions in the Jeneberang Watershed, Sulawesi, Indonesia has been eroded due to the uncontrolled use of land for vegetable farming. The objective of this paper is to determine the effects of internal and external factors on the perception and participation of farmers around the Jeneberang Watershed in Sulawesi, Indonesia. Data was analyzed by using the Structural Equation Modeling (SEM) and using Analysis of Moment Structure (AMS) version 6. Results showed that the internal factors had more significant direct effects to the farmers’ perceptions and participation, while the external factors did not significantly affect the farmers. It can be concluded that the internal factors directly and significantly influenced both the farmers’ perception and participation in the implementation of such watershed conservation. This implies that the provincial government needs to provide education and training on land use conservation for local vegetable farming. This suggests that an increase in knowledge, attitudes and skills of perception and conservation will increase farmers' participation in the implementation of conservation in vegetable farming in the Jeneberang watershed upstream.